FREQUENCY OF URETHROCUTANEOUS FISTULA FOLLOWING SNODGRASS HYPOSPADIAS REPAIR IN CHILDREN - Uzair, Muhammad; Ahmad, Munir; Hussain, Mussarat; Younus, Muhammad; Khan, Kifayat (Journal of Postgraduate Medical Institute, 2012)
Objective: To determine the frequency of urethrocutaneous fistula over a period of three months followingsnodgrass hypospadias repair for the treatment of distal penile hypospadias in children. Methodology: This descriptive study was conducted in the paediatric surgery unit, Lady Reading Hospital,Peshawar over a period of eight months from June 2009 to Febraury 2010. Patients with distal penilehypospadia without chordee between 2 and 14 years were included and patients were excluded who hadprevious repair for hypospadias. All those patients fulfilling the inclusion and exclusion criteria whoseparents gave informed consent after explanation of the whole protocol were admitted through outpatientdepartment for the said procedure and data was analyzed. Results: A total of 52 patients were included in the study. All patients were in the range of 2 to 10 yearsand underwent Snodgrass Tubularized Incised Plate (TIP) urethroplasty for hypospadias repair. The overallrate of urethrocutaneous fistula was 9 .6% (5 out of 52 patients). Mean operative time noted in minuteswas 57.52 minutes. No major morbidity or mortality was noted in this study. Conclusion: TIP urethroplasty is simple, single stage operation in the management of hypospadias and hasgood functional and low complication rate.